Tuning structures and emissive properties in a series of Zn(ii) and Cd(ii) coordination polymers containing dicarboxylic acids and nicotinamide pillars. Issue 4 (4th January 2018) - Chisca, Diana; Croitor, Lilia; Petuhov, Oleg; Kulikova, Olga V.; Volodina, Galina F.; Coropceanu, Eduard B.; Masunov, Artëm E.; Fonari, Marina S.
Abstract : The influence of the metal, ligand, and solvent on structures and emission properties was monitored. Abstract : New coordination polymers are reported. All polymers were prepared from a blend of four dicarboxylic acids, three neutral nicotinamide ligands, and Zn(ii ) or Cd(ii ) salts. The acids included: malonic (H2 mal), succinic (H2 suc), adipic (H2 adi), and 1, 4-benzenedicarboxylic (H2 bdc) acids, with all of them varying in length and rigidity of the carbon skeletons. The neutral ligands included two positional isomers, isonicotinamide (iso-nia) and nicotinamide (nia), and a nia thio-analogue, thionicotinamide (S-nia). The preparation resulted in eight Cd(ii ) and four Zn(ii ) coordination polymers: [Cd2 (suc)(sucH)2 (nia)4 ] n (1 ), [Cd(suc)(nia)3 ]·H2 O·dmf n (2 ), [Cd(adi)(iso-nia)2 ]·dmf n (3 ), [Cd(adi)(iso-nia)2 ] n, (4 ), [Zn(mal)(iso-nia)(H2 O)]·dmf n (5 ), [Cd(mal)(iso-nia)(H2 O)]·dmf n (6 ), [Zn(mal)(nia)(H2 O)]·dmf n (7 ), [Cd(mal)(nia)(H2 O)]·dmf n (8 ), [Zn(mal)(S-nia)(H2 O)]·dmf n (9 ), [Zn(bdc)(nia)2 ]·dmf n (10 ), [Cd(bdc)(nia)2 ]·dmf n (11 ), and nicotinamide-free [Cd(bdc)(H2 O)2 (dmf)]·dmf n (12 ). Compounds1–4 and12 consist of one-dimensional arrays, while compounds5–11 are two-dimensional coordination arrays. The coordination cores in1, 3, 4, 10, and11 present M2 (COO)2 (M = Zn, Cd) binuclear clusters, while the networks of2, 5–9 and12 are built on mononuclear metal nodes with nicotinamide ligands acting as double or single pillars. The structure-confirmed single crystal to single crystal transformation of3 into4 was detected and reported. While1 and4 are solvent-free apohosts, the remaining solids acted as hosts of water and dmf solvent which are accommodated in the crystal lattices as coordinated ligands or lattice solvents. The new solids were characterized by IR spectroscopy, thermogravimetric analysis, and single-crystal and powder X-ray diffraction methods. The luminescence properties of six as-synthesized coordination polymers and of some activated products are reported. The influence of the metal, ligand, and solvent on tuning the structures and emission properties was monitored, and the most impressive effects were interpreted with the help of TD-DFT computations.